Towards An Accurate Modeling of Frequency-dependent Wind Farm Components Under Transient Conditions - M. A. Abd-Allah; Mahmoud N. Ali; A. Said (International Journal of Applied Power Engineering (IJAPE), 2014)
Frequency dependence complete model is set up for describing the lightning transient behavior of the wind turbines (WTs).To get an appropriate wind turbine model, a high frequency models of surge arrester protecting the boost transformer, transformer and ground electrode soil ionization are implemented. The transient responses and Ground Potential Rise (GPR) can be obtained at different locations in the WTs and connected grid in the time domain as well as in the frequency domain using Fast Fourier Transform (FFT). To check the validity of the model, Surge arresters protection level at different locations, at i.e. LV, MV and HV, is compared with ABB manufacture data sheet, Also a comparison has been made between simple and frequency dependence model of overall wind farm components using ATP/EMTP. This paper provides an accurate simulation of wind farm components under transient condition.